O16.1 The rapid and near elimination of human papillomavirus (hpv) type 6, 11, 16 and 18 among young high-risk women within three years of the national hpv vaccination programme in australia: findings from a 10-year cross-sectional study. (13th September 2015) - Chow, EPF; Danielewski, JA; Fehler, G; Tabrizi, SN; Law, MG; Bradshaw, CS; Garland, SM; Chen, MY; Fairley, CK
Abstract : Introduction: The national quadrivalent human papillomavirus (HPV) vaccination programme was launched in Australia in April 2007. The aim of this study was to explore the proportion of vaccine targeted HPV genotypes contained in the quadrivalent (4vHPV) and the nine-valent (9vHPV) vaccines detected among young women diagnosed with Chlamydia trachomatis . Methods: Women ≤25 years attending Melbourne Sexual Health Centre from 1-July-2004 to 30-June-2014 and diagnosed with chlamydia were included in the analysis. Detection of HPV genotypes was performed on stored cervical or high vaginal samples. The proportions of women who had 4vHPV types (6/11/16/18) and the other five types within the 9vHPV grouping (31/33/45/52/58 alone) excluding 4vHPV types were calculated for each Australian financial year and stratified by age and vaccine eligibility. The proportions of HPV types among unvaccinated women in the post-vaccination period were also calculated to assess herd protection. Results: A total of 1, 202 women were included in this study. The proportion of samples with 4vHPV types dramatically decreased among Australian-born ≤25 year old females over the 10 year period (6/11 decreased from 16% to 2% [ p trend <0.001]; 16/18 decreased from 30% to 4% [ p trend <0.001]). In women ≤21 years old, HPV 6/11 remained at zero and HPV16/18 were detected in <5% of samples for all years after 2008/2009. A significant decline in 4vHPV types in unvaccinated Australian-born women was also observed, from 41.3% to 18.5% in the pre- and post-vaccination eligible periods respectively ( p = 0 .031), but no decline was seen in the other five types within the 9vHPV grouping (22.5% vs. 25.9%; p = 0 .805). Conclusion: Coverage achieved using the 3-dose vaccine was sufficient to largely eradicate 4vHPV types in Australian born women ≤21 years old, within three years of the introduction of the national HPV vaccination program. A strong herd protection was observed among women, with a significant decline in the proportion of 4vHPV in unvaccinated women. Disclosure of interest statement: EPFC has received a conference sponsorship from CSL Biotherapies. CKF has received honoraria from CSL Biotherapies and Merck and research funding from CSL Biotherapies. CKF owns shares in CSL Biotherapies the manufacturer for Gardasil. SNT and SMG are investigators on a national prevalence study of cervical cancer tissue that is receiving unrestricted funding from bioCSL, supplier of HPV vaccine in Australia. SMG has received grant support from CSL and GlaxoSmithKline, and lecture fees from Merck, GSK and Sanofi Pasteur; in addition, she has received funding through her institution to conduct HPV vaccine studies for Merck Sharp and Dohme and GlaxoSmithKline. SMG is a member of the Merck Global Advisory Board and the Merck Scientific Advisory Committee for HPV. MYC has been an investigator on investigator initiated research grants from Merck Sharp and Dohme. MGL receives unrestricted grants from Boehringer Ingelhiem, Gilead Sciences, Merck Sharp and Dohme, Bristol-Myers Squibb, Janssen-Cilag, ViiV HealthCare. All other authors have no conflicts of interest.